A Complete History of Early Christianity: Taking the “Heretics” Seriously - Franzmann, Majella (Wiley-Blackwell Publishing Asia, 2005)
The heterodox have been treated unfairly within the histories of mainstream Christian tradition, whether by their ecclesiastical opponents or by recent and current scholarship. This article outlines the place of Christian Gnostic belief and practices in the processes of self-definition and institutionalization that took place within the early history of Christianity and makes a plea to reinstate the “heretics” to their rightful place in any academic discussion of the history and beliefs of Christianity.